Assessment of Perceived Training Needs of Pack Animal Owners in the Middle Himalayan Region of India - Tanusha; Tiwari, Rupasi (International Journal of Livestock Research, 2019)
The study identified training needs of the pack animal owners in middle Himalayan region of India. The study was conducted purposively in Chamoli and Uttarkashi districts of Uttarakhand state. A total sample size of 80 respondents comprising 40 from each district was selected using snowball sampling technique. The training needs were broadly categorised into four categories viz., selection of pack animals, care and management of pack animals, training of the pack animals and knowledge about diseases of pack animals. The training regarding the knowledge about diseases of pack animals was perceived as ‘most needed’. The indicators such as first aid, treatment of diseases, vaccination and occurrence of diseases were perceived as ‘most needed’. The training about the selection of pack animals was perceived as ‘needed’ and that of training of pack animals was ‘less needed’. The respondents opined for training on care and management of pack animals as ‘not needed’.